ANÁLISE DOS DADOS DE PRECIPITAÇÃO PROVENIENTES DE DIFERENTES FONTES SOBRE A AMÉRICA DO SUL COM ÊNFASE NO BRASIL - Freitas, Ana Carolina Vasques; Franchito, Sérgio Henrique; Rao, Vadlamudi Brahmananda (CLIMEP - Climatologia e Estudos da Paisagem, 2010)
RESUMO Neste trabalho foram investigadas as potencialidades e limitações de diferentes fontes de precipitação no Brasil. Foram analisadas as semelhanças e diferenças regionais entre os valores de precipitação obtidos das estações da ANEEL (Agência Nacional de Energia Elétrica), e as séries pluviométricas obtidas da reanálise do NCEP/ NCAR (National Centers for Environmental Prediction/ National Center for Atmospheric Research) e do GPCP (Global Precipitation Climatology Project). A análise levou em conta as precipitações médias anuais e sazonais e as correlações entre as séries pluviométricas de valores medidos (estações da ANEEL) e as séries pluviométricas obtidas das outras fontes nas diferentes regiões do país. Palavras-chave: Precipitação. Fontes de dados. Climatologia. América do Sul. Regiões do Brasil. Estações Pluviométricas. ABSTRACT In this work the potentialities and limitations from different precipitation sources over Brazil were investigated. The regional similarities and differences were analyzed between the precipitation values obtained from ANEEL (National Electrical Energy Agency), and the rain gauge series obtained from the reanalysis of NCEP/NCAR (National Centers for Environmental Prediction/ National Center for Atmospheric Research) and GPCP (Global Precipitation Climatology Project). The analysis considered the average annual and seasonal precipitation and the correlations between the rain gauge series measured data (ANEEL stations) and the rain gauge series obtained from the other sources in different country regions. Keywords: Precipitation. Data Sources. Climatology. South America. Regions of Brazil. Rain Gauge. RESUMEN En este trabajo se investigó el potencial y las limitaciones de diferentes fuentes de precipitación en Brasil. Se analizaron las similitudes y diferencias regionales entre los valores de precipitación obtenidos en las estaciones de ANEEL (agencia Nacional de Energía Eléctrica), y las series pluviométricas obtenidas de reanálisis de NCEP/NCAR (National Centers for Environmental Prediction/National Center for Atmospheric Research) y del GPCP (Global Precipitation Climatology Project). El análisis tuvo en cuenta las precipitaciones medias anuales y estacionales y las relaciones entre las series pluviométricas de valores medidos (estaciones de ANEEL) y las series pluviométricas obtenidas de otras fuentes en las diferentes regiones del país. Palabras clave: Precipitación. Fuentes de los datos. Climatología. America del Sur. Regiones de Brasil. Estaciones Pluviométricas.